“It probably could've done with less plastic” - Consumers' cyclical and uneasy relationship with food packaging - Ruippo, Lotta; Kylkilahti, Eliisa; Sekki, Sanna; Autio, Minna (Frontiers in Sustainability, 2023)
Food packaging has an essential function in the contemporary food supply chain, but it is also a key source of municipal solid waste. The ability to package foods has changed eating habits as takeaway coffees, bottled water, and fast food have become more commonplace. Although the task of recycling packaging materials falls on the consumer who is guided to sort the waste and ensure it is taken to a recycling bin, the consumer perspectives of the mutually constitutive market device–consumer relationship are not yet well known. This paper studies how food shoppers are constructing their relationship with packaging in their everyday lives, and especially how their moral considerations construct the relationship with sustainability and materiality of packaging. Based on the analysis of consumer interviews, the study argues that consumers’ perspective on packaging use is renegotiated during their continuous relationship with packaging. Food packaging acts as a political market device that evokes morally charged consumer perspectives throughout different stages of consumption processes beyond the supermarket. In the first stage, the consumer is mainly focused on finding the products that have already become a part of their daily routine and the materiality of packaging oftentimes remains unseen. Tensions arise as packaging is both a source of frustration, and a necessary element of managing food consumption. After eating the food product, the packaging turns into waste and the consumer ‘becomes aware’ of the packaging materials and several negative interpretations arise. Finally, packaging waste becomes morally charged: it invites consumers to partake in recycling work and evokes environmental anxieties. The results indicate that consumers often have an uneasy, cyclical relationship with packaging use.